Tunable continuous wave Yb:CaWO4 laser operating in NIR spectral region - Yu, Hao; Chen, Chong; Li, Yong-Liang (Frontiers in Physics, 2024)
A tunable continuous wave (CW) Yb:CaWO4 laser operating in near infrared (NIR) spectral region is demonstrated by pumping with a diode laser.Continuously broadband tunable wavelengths are obtained in two polarizations by rotating the Lyot filter. The tuning widths of the output wavelengths in the πand σ-polarizations are 42 nm (from 1005.2 nm to 1047.2 nm) and 41.8 nm (from 1005.1 nm to 1046.9 nm), respectively. At an absorbed pump power of 15.6 W at 976 nm, the maximum output powers in the π-and σ-polarizations are 5.2 W at 1026.2 nm and 4.7 W at 1028.1 nm, respectively. To the best of our knowledge, this is the first tunable laser operation by using Yb:CaWO4 crystal.